Production and Evaluation of an Avian IgY Immunotoxin against CD133+ for Treatment of Carcinogenic Stem Cells in Malignant Glioma: IgY Immunotoxin for the Treatment of Glioblastoma. (2nd June 2019) - Chavez-Cortez, Elda-Georgina; Vargas Felix, Gustavo; Rangel López, Edgar; Sotelo, Julio; Martínez-Canseco, Carlos; Pérez-de la Cruz, Verónica; Pineda, Benjamin
Abstract : Background . Glioblastoma is the most common malignant tumor of Central Nervous System. Despite the research in therapeutics, the prognosis is dismal. Malignant glioma stem cells (MGSCs) are a major cause of treatment failure and increasing tumor recurrence. In general, cancer stem cells (CSCs) express prominin-1 (CD133), considered as a potential therapeutic target. In this study, we produced an avian immunotoxin directed against the subpopulation of CD133+ CSCs within a malignant glioma. We used the avian IgY because it has various advantages as increased affinity to mammal antigens and inexpensive obtention of large amounts of specific antibodies (approximately 1 mg/per egg). The design, production, purification and use of IgY anti CD133 immunotoxin constitute an original goal of this research. Methods . The immunodominant peptide of CD133 was designed to immunize hens; also, the extracellular domain of CD133 was cloned to probe the IgY antibodies. In parallel, a recombinant abrin A chain was produced in E. coli in order to join it to the Fc domain of the anti-CD133 IgY to conform the immunotoxin. This anti-CD133 IgY anti-tumor immunotoxin was tested in vitro and in vivo. Results . The cytotoxicity of the immunotoxin in vitro showed that IgY-abrin immunotoxin reduced 55% cell viability. After subcutaneous MGSCs implantation, the animals treated intraperitoneally or intratumorally with the IgY-abrin immunotoxin showed more than 50% decrease of tumor volume. Conclusion . Results showed that the IgY-abrin immunotoxin had cytotoxic activity against CD133+ MGSCs and provides a novel approach for the immunotherapy of glioblastoma.